Hepcidin response to interval running exercise is not affected by oral contraceptive phase in endurance-trained women - Alfaro-Magallanes, V. M.; Barba-Moreno, L.; Rael, B.; Romero-Parra, N.; Rojo-Tirado, M. A.; Benito, P. J.; Swinkels, D. W.; Laarakkers, C. B.; Díaz, A. E.; Peinado, A. B. (Scandinavian Journal of Medicine & Science in Sports, 2021)
The use of oral contraceptives (OCs) by female athletes may lead to improved iron status, possibly through the regulation of hepcidin by sex hormones. The present work investigates the response of hepcidin and interleukin-6 (IL-6) to an interval exercise in both phases of the OC cycle. Sixteen endurance-trained OC users (age 25.3 ± 4.7 years; height 162.4 ± 5.7 cm; body mass 56.0 ± 5.7 kg; body fat percentage 24.8 ± 6.0%; peak oxygen consumption [VO2peak]: 47.4 ± 5.5 mL min-1 kg-1) followed an identical interval running protocol during the withdrawal and active pill phases of the OC cycle. This protocol consisted of 8 × 3 minutes bouts at 85% VO2peak speed with 90 seconds recovery intervals. Blood samples were collected pre-exercise, and at 0 hour, 3 hours, and 24 hours post-exercise. Pre-exercise 17ß-estradiol was lower (P = .001) during the active pill than the withdrawal phase (7.91 ± 1.81 vs 29.36 ± 6.45 pg/mL [mean ± SEM]). No differences were seen between the OC phases with respect to hepcidin or IL-6 concentrations, whether taking all time points together or separately. However, within the withdrawal phase, hepcidin concentrations were higher at 3 hours post-exercise (3.33 ± 0.95 nmol/L) than at pre-exercise (1.04 ± 0.20 nmol/L; P = .005) and 0 hour post-exercise (1.41 ± 0.38 nmol/L; P = .045). Within both OC phases, IL-6 was higher at 0 hour post-exercise than at any other time point (P < .05). Similar trends in hepcidin and IL-6 concentrations were seen at the different time points during both OC phases. OC use led to low 17ß-estradiol concentrations during the active pill phase but did not affect hepcidin. This does not, however, rule out estradiol affecting hepcidin levels.